Key Risk Factors Contributing to Postpartum Depression: Literature Review - Alfahal, Mohammed; Alfahal, Mohammed Salah (International Journal of Innovative Research in Medical Science, 2024)
Postpartum depression (PPD) is prevalent and debilitating mood disorder that affects women during the postpartum period and severely impact maternal-infant bonding, child development, and family dynamics. This review aimed to provide a comprehensive analysis of the key risk factors contributing to the onset of Postpartum depression. The review investigated the latest research findings on risk factors leading to postpartum depression to inform clinical practice and public health strategies, ultimately enhancing prevention, early detection, and intervention. To reduce the burden of Postpartum depression and improve outcomes for mothers, children and families, this review highlighted the need for addressing these diverse factors through integrated, culturally sensitive, and multidisciplinary approaches. Additional research endeavors are needed to delve deeper into the comprehensive spectrum of causes, progression, outcomes of postpartum depression, mitigation of its effects, and the development of effective strategies to preclude its onset.